Encoding and Encryption of Digital Cinema Package - Philip, Jithu; Raju, Merin (Indian Journal of Computer Science, 2019)
During the past decade it became the use of digital formats became widespread in the production, post production, and distribution process in the film industry. Digital cinema package is one of the widely accepted and commonly used formats in the distribution of digital cinema. This paper specifies the key details and attributes of digital cinema package along with the encoding and encryption process used in digital cinema package creation. Most commonly used approaches in digital cinema distribution are discussed in the later section of the document. The evaluation of encoding of the digital cinema package is based on a practical approach and the experimental results obtained are also discussed.